Real Wages in Manufacturing, 1890-1914 - Rees, Albert (Princeton Legacy Library, 2016)
Previous wage studies of the period before World War I found that real wages remained stable from 1890 to 1914 despite the continued growth of the economy. This study indicates that this conclusion was based on faulty statistics. Using new estimates of money wages and a new cost-of-living index, Mr. Rees shows that real wages rose considerably in this period, although less than in later years. His findings will require revision of the prevailing viewpoint. Originally published in 1961. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.